Fluorescence‐Based Detector Design Principles for Low Vapor Pressure Analytes - Alex S. Loch; Paul L. Burn; Paul E. Shaw (Advanced Sensor Research)
Abstract Fluorescence‐based sensing is a promising method for detecting trace quantities (vapors) of chemical threats. However, direct detection at standard temperature and pressure of chemicals with low volatilities, such as the salts of illegal drugs, is difficult to achieve. Herein, the development of a testing platform designed to maximize the response from fluorescent material detection of low volatility analytes, using the salts of illicit drugs as exemplars, is described. The challenges encountered in detecting low‐volatility analytes are highlighted, and the hardware solutions employed to overcome them are detailed. The testing platform is composed of a swab heating unit, a sensing chamber, and optical components that enable detection of illicit drugs via a fluorescence quenching mechanism. The swab heating unit facilitates volatilization of the analytes, with the shape of the sensing chamber and its fabrication material optimized to maximize the interaction of the analyte with the sensing element, increasing sensitivity. The detection platform is able to detect trace amounts (down to 30 ng) of (±)‐3,4‐methylenedioxyamphetamine hydrochloride (MDA•HCl), along with other common illicit drug salts such as cocaine hydrochloride (cocaine•HCl), fentanyl•HCl, and methamphetamine•HCl (MA•HCl).